Peran Dan Kedudukan Ombusman Sebagai Lembaga Perlindungan Rakyat Dalam Mewujudkan Asas-Asas Umum Pemerintahan Yang Baik - cholidah utama (Medina-te : Jurnal Studi Islam, 2018)
The inclusion of the Ombudsman in the Amendment to the 1945 Constitution will place the existence of the Ombudsman's recommendations philosophically (as well as politically) with high value. So that even though it is not legally binding, it is still obeyed by the State Administration. The position of the Ombudsman is a state institution that is independent and does not have an organic relationship with state institutions and other government agencies, and in carrying out its duties and authority free from interference from other powers.